Pengaruh Video Edukasi Sleep Hygiene dan Online Sleep Diary pada Peningkatan Kualitas Tidur Mahasiswa STIKes Binalita Sudama Medan - Astuti, Tani; Rahmini, Juwi Athia; Ulfa Hanim; Suryanto, Bambang; Siregar, Tuful Zuchri; Martiningsih (Bima Nursing Journal, 2025)
Students are a vulnerable age group with academic responsibilities, which puts them at risk of sleep problems. Student sleep problems are associated with various challenges such as high academic pressure, social obligations, social media distractions, responsibilities, and varied schedules. Students have poor sleep quality due to personal and environmental factors. Students extensively use technology in the learning process for communication. Videos enhance the learning process and yield better learning outcomes. The use of educational videos also increases student engagement and participation in understanding topics more effectively and enhances interest in the learning process. Therefore, sleep hygiene education through videos and online sleep diaries will be highly beneficial in improving students’ sleep quality. Similar research has not yet been conducted at STIKes Binalita Sudama Medan. The aim was identify the impact of educational videos on sleep hygiene and online sleep diaries on improving students’ sleep quality. This study employed a quasi-experimental design with a control group, using purposive sampling on 15 respondents in the intervention group and 15 respondents in the control group. The measurement tool used was the Pittsburgh Sleep Quality Index questionnaire. Statistical analysis was conducted using a t-test. The study showed educational videos on sleep hygiene and online sleep diaries significantly influenced the improvement of sleep quality among students at STIKes Binalita Sudama. Implementing educational videos for students experiencing sleep issues and evaluating sleep problems after implementing sleep hygiene education and online sleep diaries can improve students’ sleep quality.